Zambia : Post-Privatization Study - Serlemitsos, John; Fusco, Harmony (World Bank, Washington, DC, 2014)
The World Bank seeks to assess the effectiveness of the privatization program which was initiated in Zambia in 1992 with significant assistance from the World Bank and other donor agencies. A review of representative sample of companies was undertaken in order to assess the effect of privatization on performance. The twenty largest non-copper mining companies by purchase price, the twenty by current assets at time of privatization, and a remaining sample of smaller companies were chosen for the study. The indicator most consistently reported by companies was turnover. This indicator was chosen as the most reliable available gauge for analysis of performance. Typically smaller and less export-oriented - the initial benefits of privatization have been difficult to sustain, and performance has faltered after the initial two years. Although recent performance has been better than in the immediate pre-privatization period, turnover among most companies has never recovered in real terms to early 1990 levels. Difficulty in sustaining the net benefits of privatization can also be attributed to a suboptimal domestic and regional environment for private sector growth. Greater attention to these constraints within the domestic and regional environment is warranted in future World Bank assistance strategies, in order to enhance the benefits of privatization and maximize new private sector growth.